2019
DOI: 10.4236/as.2019.109087
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Trade in Donkey Hide: An Opportunity or a Threat for Communities in Kenya?

Abstract: Donkey hides are used in a form of Traditional Chinese medicine called ejiao, the demand for ejiao is currently so high the global donkey population is currently in decline. Africa's donkey population is considered a key source for the trade, with Kenya being highlighted as being particularly affected. In Kenya donkeys play a vital contribution to people's livelihoods; this study aimed to explore the potential impact of the donkey hide trade on small holder farmer's livelihoods. The study was conducted in five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…As discussed later, more research is needed to quantify the current and potential impacts on communities’ livelihoods and well‐being; however some research has begun to explore this. One study conducted in Kenya found that participants reported that the sale of their donkeys provided them with an initial cash boost, which they could use to pay medical bills and education fees (Carder et al 2019). However, there was a reported long term negative effect on food security, therefore it is likely that the breeding and selling of donkeys by small holder farmers is not a sustainable livelihood option (Carder et al 2019).…”
Section: Impact On Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed later, more research is needed to quantify the current and potential impacts on communities’ livelihoods and well‐being; however some research has begun to explore this. One study conducted in Kenya found that participants reported that the sale of their donkeys provided them with an initial cash boost, which they could use to pay medical bills and education fees (Carder et al 2019). However, there was a reported long term negative effect on food security, therefore it is likely that the breeding and selling of donkeys by small holder farmers is not a sustainable livelihood option (Carder et al 2019).…”
Section: Impact On Communitiesmentioning
confidence: 99%
“…One study conducted in Kenya found that participants reported that the sale of their donkeys provided them with an initial cash boost, which they could use to pay medical bills and education fees (Carder et al 2019). However, there was a reported long term negative effect on food security, therefore it is likely that the breeding and selling of donkeys by small holder farmers is not a sustainable livelihood option (Carder et al 2019). This is because supply cannot meet demand, and there is an increased purchase price of donkeys.…”
Section: Impact On Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study was conducted in five counties in Kenya by Carder et al (2019) on the emerging trade in donkey hide. The study assessed both opportunity and threat for communities.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In a study published in 2019 by the Kenya Agricultural and Livestock Research Organization (KALRO), the annual number of donkeys slaughtered in Kenya was five times higher than the annual donkey population growth rate which, if neither rate changed, would lead to the complete extinction of the Kenyan donkey population by 2023 (Kenya Agriculture and Livestock Research Organization, 2019). The trade also threatens the livelihoods of vulnerable communities, particularly women, who will often be left carrying the load that a donkey would have (Carder et al, 2019;Brooke, 2014). Smallholder farmers lose an average of USD 109.73 per month for every donkey they lose through sale or theft (Brooke, 2019) with many families unable to send children to school or pay medical bills due to loss of income.…”
mentioning
confidence: 99%